Genomic mapping for grain yield, stay green, and grain quality traits in sorghum - Sukumaran, Sivakumar (Kansas State University, 2012)
Knowledge of the genetic bases of grain quality traits will complement plant breeding efforts to improve the end use value of sorghum (Sorghum bicolor (L.) Moench). The objective of the first experiment was to assess marker-trait associations for 10 grain quality traits through candidate gene association mapping on a diverse panel of 300 sorghum accessions. The 10 grain quality traits were measured using the single kernel characterization system (SKCS) and near-infrared reflectance spectroscopy (NIRS). The analysis of the accessions through 1,290 genome-wide single nucleotide polymorphisms (SNPs) separated the panel into five subpopulations that corresponded to three major sorghum races (durra, kafir, and caudatum), one intermediate race (guinea-caudatum), and one working group (zerazera/caudatum). Association analysis between 333 SNPs in candidate genes/loci and grain quality traits resulted in eight significant marker-trait associations. A SNP in starch synthase IIa (SSIIa) gene was associated with kernel hardness (KH) with a likelihood ratio–based R[superscript]2 (R[subscript]L[subscript]R[superscript]2) value of 0.08. SNPs in starch synthase (SSIIb) gene (R[subscript]L[subscript]R[superscript]2 = 0.10) and loci pSB1120 (R[subscript]L[subscript]R[superscript]2 = 0.09) was associated with starch content. Sorghum is a crop well adapted to the semi arid regions of the world and my harbor genes for drought tolerance. The objective of second experiment was to identify quantitative trait loci (QTLs) for yield potential and drought tolerance. From a cross between Tx436 (food grain type) and 00MN7645 (drought tolerant) 248 recombinant inbred lines (RILs) was developed. Multi-location trials were conducted in 8 environments to evaluate agronomic performance of the RILs under favorable and drought stress conditions. The 248 RILs and their parents were genotyped by genotyping-by-sequencing (GBS). A subset of 800 SNPs was used for linkage map construction and QTL detection. Composite interval mapping identified a major QTLs for grain yield in chromosome 8 and QTL for flowering time in chromosome 9 under favorable conditions. Three major QTLs were detected for grain yield in chromosomes 1, 6, and 8 and two flowering time QTLs on chromosome 1 under drought conditions. Six QTLs were identified for stay green: two on chromosome 4; one each on chromosome 5, 6, 7, and 10 under drought conditions.
Keywords: Sorghum; Drought; Stay green; QTL mapping; Association mapping; Agronomy (0285)